Easy, Simple, Lower Cost -Heat Transfer Kit: A Case Study of Implementation and Student Response - Masta, Ngia; N. Aruan, Bunga; Faradiba; Sianturi, Manogari (Laboratory Journal : Jurnal Laboratorium Sains Terapan, 2025)
The low level of scientific literacy in Indonesia has prompted efforts to improve the quality of science education, particularly through the promotion of science process skills. Practical activities such as experiments and hands-on investigations are indicators of science skill–based learning. However, their implementation is often limited by the lack of adequate laboratory equipment. This study introduces a simple, low-cost experimental kit designed to facilitate the teaching of heat and its transfer processes, specifically for the senior high school level. The study describes the kit construction, provides conceptual explanations of the underlying physics, and examines student participation during learning activities conducted with the Discovery Learning model. A case study approach was employed, with qualitative data collected through classroom observations and informal interviews. The findings indicate that students actively engaged throughout the learning process, from assembling the kit to conducting group experiments. They were able to directly observe heat transfer phenomena through conduction, convection, and radiation. This hands-on experience enhanced their conceptual understanding, as reflected in their ability to confidently explain experimental results during class discussions. The study concludes that the Simple Heat Transfer Kit can serve as an effective alternative medium for teachers to implement science skill–based learning, thereby improving both student participation and conceptual comprehension, particularly on the topic of heat transfer.